EP.WE.409Stoma forming surgery – has lockdown changed our operative practice during COVID 19. (28th October 2021) - Manson, Ross; Tallo, Tracy; Robertson, Isabell; Anderson, John; Sharma, Praveen; MacDonald, Angus
Abstract: Aims: This study aimed to establish whether the initial lockdown resulted in a shift towards emergency surgery, changes in stoma formation and in rate of surgery with curative intent. Methods: A retrospective data collection was performed. Patients were identified using a local database of all patients with stomas. Data was collected from 16/03/20 to 16/09/20. A comparison data set was taken (16/03/19 to 16/09/19). Data was collected on whether the case was performed as an emergency; the type of stoma formed and whether the operation was performed with curative intent. Results: Seventeen patients were identified in the 2020 cohort (age: 51-84, mean age: 67.6, M:F 10:7). Fourteen cases (82.4%) were performed as emergencies, three electively (17.6%). Six (35.3%) had end colostomies, three (17.6%) had loop colostomies, one (5.9%) had a caecostomy, four (23.5%) had an end ileostomy and three (17.6%) had a loop ileostomy. Ten operations were for patients with cancer, three (30%) were performed with curative intent. 38 patients were identified in the 2019 cohort (age: 28-85, mean age: 63.0, M:F 17:21). 23 (60.5%) were emergencies, fifteen (39.5%) were performed electively. Nine (23.7%) had end colostomies, eight (21.1%) had loop colostomies, three (7.9%) had caecostomies, ten (26.3%) had end ileostomies and nine (23.7%) had loop ileostomies. There were nineteen operations for cancer, eight (42.1%) were with curative intent. Conclusions: Cessation of elective activity caused a shift towards emergency operating, with an associated shift towards surgery with non-curative intent. The distribution of stomas formed has not changed.